1985
DOI: 10.1055/s-2007-969577
|View full text |Cite
|
Sign up to set email alerts
|

Acetoxychavicol Acetate, an Antifungal Component ofAlpinia galanga1

Abstract: The essential oils from fresh and dried rhizomes of ALPINIA GALANGA showed an antimicrobial activity against gram-positive bacteria, a yeast and some dermatophytes, using the agar overlay technique. The main components of the oils were also tested and terpinen-4-ol was found most active. An N-pentane/diethyl ether extract of dried rhizomes was active against TRICHOPHYTON MENTAGROPHYTES. 1'-Acetoxychavicol acetate, 1'-acetoxyeugenol acetate and 1'-hydroxychavicol acetate identified by MS and NMR were found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 7 publications
5
72
0
2
Order By: Relevance
“…Study of Kiaei et al showed that in the disk diffusion method, 100 mg/ml of U. dioica L. completely inhibited the growth of grampositive bacteria isolated from patients with UTI, but did not affect E. coli (2). In 1985, Janssen et al stated that nettle's extract inhibited the growth of S. aureus and S. epidermidis (9). Study of Kavalali in 2003 reported that the ethanolic extract of nettle inhibited the growth of S. aureus (28), consistent with the findings of the present study.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Study of Kiaei et al showed that in the disk diffusion method, 100 mg/ml of U. dioica L. completely inhibited the growth of grampositive bacteria isolated from patients with UTI, but did not affect E. coli (2). In 1985, Janssen et al stated that nettle's extract inhibited the growth of S. aureus and S. epidermidis (9). Study of Kavalali in 2003 reported that the ethanolic extract of nettle inhibited the growth of S. aureus (28), consistent with the findings of the present study.…”
Section: Resultssupporting
confidence: 86%
“…Also, this study showed that the plant extract completely inhibited the growth of gram-positive bacteria such as Staphylococcus epidermidis, Staphylococcus aureus and Staphylococcus saprophyticus, while E. coli was resistant to the extract (2). Another study found that the alcoholic extract of the plant have favorable antibacterial activity against Streptococcus pyogenes, S. aureus and S. epidermidis (9). Different parts of this plant contains chlorophyll, vitamins (C, K, B1, B2), pantothenic acid, carotenoid, protein, tannin, essential oils, minerals (iron, manganese, copper and nickel), acetylcholine, histamine, flavonoids (10), phenolic acids and alkaloids (11).…”
Section: Introductionmentioning
confidence: 99%
“…Janssen;Scheffer (1985) e Matasyoh et al (2007) atribuem a 4-terpineol e 1,8-cineol a capacidade de inibir vários micro-organismos agindo, esse último, também contra S. aureus (Gachkar et al, 2007). Segundo Oonmetta-Aree et al (2006), a ação antimicrobiana pode estar relacionada à presença de sesquiterpenos em folhas, raízes e flores de espécies da família Zingiberaceae.…”
Section: Resultsunclassified
“…It has been reported that 1′-ACA possesses various biological activities, such as antitumor (Itokawa et al, 1987;Kondo et al, 1993;Moffatt et al, 2000;Zheng et al, 2002;Ito et al, 2005;Azuma et al, 2006;Campbell et al, 2007), anti-inflammation (Nakamura et al, 1998;Morikawa et al, 2005), antifungal (Janssen & Scheffer, 1985), antiviral (Ye & Li, 2006), antioxidative (Kubota et al, 2001), and xanthine oxidase inhibitory activity (Noro et al, 1988). Although it has been reported that the ethanol extract of A. galanga exhibits antibacterial activity against S. aureus (Oonmetta-aree et al, 2006), the antibacterial activity of 1′-ACA has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%